The Labor Concept of Marx, Calvin, Luther in the Framework of Legal or Religious Rights - Silvana, Ago (European Journal of Multidisciplinary Studies, 2016)
The most recent studies on economic ethics of world religions try to remind us once again the link between religion and economics in social rights, as one of the most important links of social stratification. The desire and passion to approach the idea of the man, who wants to live with both the matter and the spiritual, brings us to rethink once again that man needs a new social and religious spirit at the same time. As a scholar of religion and morality Weber shows the relation between religion, labor, and the right. It can never be left out without clarifying the problem that we are inspired by a new course “the opportunity to own" what we want. One can never abandon the idea that inspiration coming from religion brings a new level – a profession, which basically makes you who you are as a professional. We try to understand a new situation that basically is less complicated “intuition”. No matter how much we want to be pure in what we see in intuition, it isn’t clear in religion. Maybe the obstacle that the religion wants to present to intuition is much stronger than that. “The intuition” regarding the human being seems to be an intuition, to be grasped through your own intelligence, whereas the intuition comprehended as religion, through new ways brings a more complicated situation than this. – It brings us a situation when one choice makes you lose control. The narrowing of these two gaps which are seen both with the right to work as well as the right to have a new inspiration under the order of labor, leads to the desire to see Marx, Calvin and Luther as the Reformers of the rule of social relationships under the right of religious morality.